Intravascular Coagulation with Generalized Shwartzman Reaction Induced by Liquoid: Lack of Protection by Extreme Thrombocytopenia - Evensen, S. A; Jeremic, M (Thrombosis and Haemostasis, 1968)
The role of platelets in the triggering of intravascular coagulation has been studied by comparing the effects of Liquoid in normal and in thrombocytopenic rabbits. Thrombocytopenia was induced by intraperitoneal injections of the alkylating agent Busulphan. The mean platelet count in a group of 16 thrombocytopenic animals was 9,000/mm3 (range 0–25,000/mm3).An intravenous injection of 20 mg Liquoid/1500 g body weight produced in both groups a progressive depletion of fibrinogen and factor V, a transient fall of factor VII, and the generalized Shwartzman reaction. In the thrombocytopenic animals, however, the clotting defects and the kidney lesions were less severe than in the controls.We conclude that the triggering effect of Liquoid is not mediated through release of clot-initiating activity from platelets alone. Platelets – at least in this experimental model – appear to accelerate intravascular coagulation, but not to initiate it.